Dermatologic Simulation of Neglected Tropical Diseases for Medical Professionals - Michael Mankbadi; Laura Goyack; Bryan Thiel; David Weinstein; Judith Simms-Cendan; Caridad Hernandez (Association of American Medical Colleges, 2016)
Abstract Introduction While patients with neglected tropical diseases may present for care in the United States, they are encountered so infrequently that medical professionals may have little chance of being exposed to these illnesses during training. This simulation on dermatological presentations of neglected tropical diseases was used as a teaching tool for multifaceted topics including disease management, interdisciplinary collaboration, and sociocultural issues. To achieve this goal, we created four cases with patients demonstrating clinical and dermatological presentations. Methods Through the use of a moulage kit, this simulation portrayed four common neglected tropical diseases that are rarely encountered in the United States: dengue fever, cutaneous leishmaniasis, lepromatous leprosy, and yaws. Following the clinical experience, a debrief session discussing sociocultural and dermatological factors of neglected tropical diseases occurred. Results The feedback obtained regarding the simulation was exceptionally positive. The participants indicated that the simulation improved their medical knowledge of neglected tropical diseases, diagnostic abilities, and interprofessional communication skills. Discussion This simulation can easily be adapted for use in conferences, health professional education, and patient advocacy, making it relevant for training in a wide variety of settings. Through the application of this simulation, greater progress can be made in the education of medical professionals on neglected tropical diseases and dermatology. Not only will the application of realistic workshops increase medical competency regarding these rarely encountered diseases, it will also provide opportunities to engage with these diseases, which can cultivate interest in the future pursuit of global health.